Drawing Atelier the figure : how to draw in a classical style - DeMartin, Jon (Cincinnati, Ohio North Light Books, 2016)
"In this book, one of today's leading figurative artists shares techniques and approaches for drawing the human form. With a reverent grounding in the methods of the Old Masters and keen perspective developed over Jon DeMartin's 20+ years of making and teaching art, this comprehensive workshop focuses on the power of line and how it can be used to achieve a convincing sense of dimension and life.Beautifully illustrated with classical drawings as well as step-by-step progressions, these lessons explore the enlightening practice of copying, how to use proportion and measurement wisely, drawing the head and its features, rendering the figure in motion, short-pose exercises, and much, much more"--Provided by publisher.
Keywords: Figure drawing -- Technique; Drawing -- Technique; Human figure in art